Student Learning Interest Through Speed Cone Game: Descriptive Study at Junior High School 5 Banjarbaru - Hafidz Ibnu Fahrezy; Mita Erliana; Perdinanto; Akhmad Amirudin (Jurnal Master Penjas & Olahraga, 2026)
This study aimed to determine whether the Speed Cone game could improve students’ interest in learning running activities at SMP Negeri 5 Banjarbaru. The research employed a quantitative descriptive approach using a survey method. The population consisted of all students participating in physical education learning, while the sample comprised 31 students selected as research participants. Data were collected using an interest-in-learning questionnaire and observation sheets as the research instruments. The findings revealed that the implementation of the Speed Cone game successfully increased students’ learning interest in athletics, particularly running. The results showed that 58.1% of students were in the high category, 25.8% were in the very high category, and 16.1% were in the moderate category, with no students classified in the low or very low categories. It can be concluded that the Speed Cone game is an effective and innovative learning strategy for enhancing students’ interest in physical education learning.